Technological advances in the production of carotenoids and their applications– A critical review. (January 2023) - Ashokkumar, Veeramuthu; Flora, G.; Sevanan, Murugan; Sripriya, R.; Chen, W.H; Park, Jeong-Hoon; Rajesh banu, J.; Kumar, Gopalakrishnan
Graphical abstract: Highlights: Recent developments in the extraction and purification of carotenoids were presented. Explored the metabolic engineering approaches in carotenoids synthesis. Application of carotenoids in pharmaceutical and nutraceuticals industries. The global market value of astaxanthin production has been presented. Abstract: Carotenoids are naturally occurring pigments that are widely distributed in algae, fungi, bacteria, and plants. Carotenoids play a significant role in the food, feed, cosmetic, nutraceutical, and pharmaceutical industries. These pigments are effectively considered as a health-promoting compounds, which are widely used in our daily diet to reduce the risk of chronic diseases such as cardiovascular diseases, cancer, acute lung injury, cataracts, neural disorders, etc. In this context, this review paper demonstrates the synthesis of carotenoids and their potential application in the food and pharmaceutical industries. However, the demand for carotenoid production is increasing overtime, and the extraction and production are expensive and technically challenging. The recent developments in carotenoid biosynthesis, and key challenges, bottlenecks, and future perspectives were also discussed to enhance the circular bioeconomy.